Evaluation of Automatic Densitometer with Laser Diode - Larrea Cox, Pedro J.; Hernández Tabares, Lorenzo; Suárez San Pedro, Cirilo E.; Vázquez Cano, Aradys; de los Reyes Rodríguez, Marlén (Revista Cubana de Física, 2010)
The evaluation of a prototype of an automatic scanning densitometer, transmission mode, is presented. It contains a semiconductor diode laser as light source, is primarily intended for analysis of protein electrophoresis, and was developed at the Center for Technological Applications and Nuclear Development (CEADEN). Its technical specifications were determined and certified in the National Institute of Researches on Metrology (INIMET), and also the equipment was tested at the Laboratory of Process Control on Company of Sera and Blood Products “Adalberto Pesant”, in Havana, where it was used to control the quality of intermediate products that are produced there, obtaining satisfactory results.